2023
DOI: 10.3390/molecules28196881
|View full text |Cite
|
Sign up to set email alerts
|

Essential Components from Plant Source Oils: A Review on Extraction, Detection, Identification, and Quantification

Muhammad Abdul Rahim,
Hudda Ayub,
Aqeela Sehrish
et al.

Abstract: Oils derived from plant sources, mainly fixed oils from seeds and essential oil from other parts of the plant, are gaining interest as they are the rich source of beneficial compounds that possess potential applications in different industries due to their preventive and therapeutic actions. The essential oils are used in food, medicine, cosmetics, and agriculture industries as they possess antimicrobial, anticarcinogenic, anti-inflammatory and immunomodulatory properties. Plant based oils contain polyphenols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 300 publications
0
7
0
Order By: Relevance
“…Organic acids like oxalic acid, maleic acid, citric acid, tartaric acid, malic acid, ascorbic acid, shikimic acid, and fumaric acid are present in the examined fruit. The aqueous extract of the green variety showed higher levels of malic and citric acid when compared with the pink and sweet varieties of C. carandas [35,36]. Evidence suggests that organic acids such as malic or citric acids act as antioxidants and esters, with an increasing number of commercial applications as organic compounds [37].…”
Section: Discussionmentioning
confidence: 99%
“…Organic acids like oxalic acid, maleic acid, citric acid, tartaric acid, malic acid, ascorbic acid, shikimic acid, and fumaric acid are present in the examined fruit. The aqueous extract of the green variety showed higher levels of malic and citric acid when compared with the pink and sweet varieties of C. carandas [35,36]. Evidence suggests that organic acids such as malic or citric acids act as antioxidants and esters, with an increasing number of commercial applications as organic compounds [37].…”
Section: Discussionmentioning
confidence: 99%
“…cremoris. All kinds of cheeses were produced according to the standard protocol of cheddar cheese production and were ripened at 6-8 • C for the duration of 90 days and analyzed at pre-set intervals of 0, 45, and 90 days [14].…”
Section: Cheddar Cheese Production and Experimental Planmentioning
confidence: 99%
“…Safflower is produced in several countries of the world; it has already been used for a large number of food and medicinal applications. In comparison to all dietary lipids, it possesses the highest concentration of LA 85% fatty acid [14]. Safflower oil has a pale yellow color with an almost bland flavor and its suitability as a substrate for the conversion of LA to CLA in cheddar cheese needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chia seed oil (CSO) contains large amounts of alpha-linolenic acid (ALA) and linoleic acid. CSO is a rich source of natural antioxidants like various types of tocopherols, bioactive or polyphenol compounds, and phytonutrients . On the other hand, fish oil (FO) (Labeo rohita) is obtained from fish fillet, which has been recognized as a good source of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) contents.…”
Section: Introductionmentioning
confidence: 99%
“…CSO is a rich source of natural antioxidants like various types of tocopherols, bioactive or polyphenol compounds, and phytonutrients. 7 On the other hand, fish oil (FO) ( Labeo rohita ) is obtained from fish fillet, which has been recognized as a good source of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) contents. Many studies have shown that fish fillets contain up to 30% oil, including EPA (18%) and DHA (12%), respectively.…”
Section: Introductionmentioning
confidence: 99%